Joyful noise poems for two voices - Fleischman, Paul; Beddows, Eric (New York Harper Collins, 1988)
A collection of poems describing the characteristics and activities of a variety of insects
"A Charlotte Zolotow book."
American Corner
Awarded John Newbery Medal
11
NEW_DMN_GN
Keywords: American poetry; Children's poetry; Insects -- Poetry; Poetry